Comparing parent and teacher ratings of emotional and behavioural difficulties in 5-year old children who are deaf or hard-of-hearing. (2nd January 2020) - Wong, Cara L.; Ching, Teresa YC; Cupples, Linda; Leigh, Greg; Marnane, Vivienne; Button, Laura; Martin, Louise; Whitfield, Jessica; Gunnourie, Miriam
ABSTRACT: Children who are deaf or hard of hearing (DHH) are at higher risk of developing mental health problems. This study reports on the parent and teacher ratings of emotional and behavioural difficulties (EBD) in 5-year old DHH children. It explores the similarities and differences between informants, and the risk and protective factors associated with parent and teacher-ratings of EBD. Parents and teachers of 224 DHH children completed questionnaires on children's EBD and functional auditory behaviour. Children completed standardized assessments of non-verbal cognitive and language abilities. On average, parent- and teacher-rated EBD were 0.42 and 0.20 standard deviations higher than typically developing children. Parents reported more behavioural problems (hyperactivity and conduct), whereas teachers reported poorer prosocial behaviour. Inter-rater correlations were generally low to moderate (0.29 to 0.50). Overall, children with additional disabilities, lower non-verbal cognitive ability, and poor functional auditory behaviour were at higher risk of EBD. Language ability was only a significant predictor of teacher-rated EBD for children with hearing aids but not cochlear implants. Differences in informant-ratings emphasize the need for a multi-informant approach to get a global perspective on the psychopathology of DHH children. The findings indicate that parents may need assistance with managing behavioural problems at home, and teachers should facilitate more opportunities to practice prosocial behaviour at school. Intervention efforts should focus on facilitating good functional listening skills, as this may in turn, improve the mental health of young DHH children.